Digital Mindset and the Transformation of Family Business Management in Advancing SMEs’ Circular Business Practices toward the SDGs: A Systematic Literature Review (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Global economic developments show the acceleration of the adoption of circular business models, where resource efficiency and waste reduction are the main focuses to answer sustainability demands and SDGs targets. Although this trend is strengthening globally, MSMEs, especially those based on family businesses, are still lagging behind in their implementation, even though digitalization is increasingly opening up opportunities for operational optimization and innovation. The urgency of this research arises from the need to understand how the digital mindset and transformation of family business management can accelerate the readiness of MSMEs in implementing circular business practices. The novelty of this research lies in the integration of the three strategic concepts into a single analytical framework through the Systematic Literature Review (SLR), a perspective that has rarely been combined in previous studies. With the SLR method based on the PRISMA protocol, this study shows that MSMEs already have a strong foundation in the digital mindset, including technology readiness, innovation orientation, and adaptation of digital business models. Family business values have also been proven to support business continuity through knowledge transfer and long-term investment. However, the implementation of circular business practices is still weak, especially in resource cycle management, sustainable product design, and environmental impact measurement. The implication is that the synergy of digital mindset and family business governance can strengthen the transition of MSMEs to a circular economy that directly supports the achievement of the SDGs, especially in the areas of sustainable consumption-production and industrial innovation.